2014
DOI: 10.1161/circulationaha.114.010434
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor–Mediated Cardiac Contractility Is Inhibited via Vasopressin Type 1A-Receptor–Dependent Signaling

Abstract: Background Enhanced arginine vasopressin (AVP) levels are associated with increased mortality during end-stage human heart failure (HF), and cardiac AVP type 1A receptor (V1AR) expression becomes increased. Additionally, mice with cardiac-restricted V1AR overexpression develop cardiomyopathy and decreased β-adrenergic receptor (βAR) responsiveness. This led us to hypothesize that V1AR signaling regulated βAR responsiveness and in doing so contributes to HF development. Methods and Results Transaortic constri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 56 publications
(63 reference statements)
3
37
0
Order By: Relevance
“…Tissues were quickly frozen in liquid nitrogen and stored at -80°C until use. Membrane proteins were prepared as described previously (38). In brief, tissue was lysed in buffer (Cell Signaling Technologies) containing protease and phosphatase inhibitor cocktail (ThermoScientific) and homogenized with beads in a Bullet Blender (Next Advance).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissues were quickly frozen in liquid nitrogen and stored at -80°C until use. Membrane proteins were prepared as described previously (38). In brief, tissue was lysed in buffer (Cell Signaling Technologies) containing protease and phosphatase inhibitor cocktail (ThermoScientific) and homogenized with beads in a Bullet Blender (Next Advance).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, tissue was lysed in buffer (Cell Signaling Technologies) containing protease and phosphatase inhibitor cocktail (ThermoScientific) and homogenized with beads in a Bullet Blender (Next Advance). NMVCs were rinsed with ice-cold PBS, collected, and lysed in buffer (38). After centrifugation at 13,000 g for 5 minutes at 4°C, the supernatant was collected and protein levels were determined by Bradford assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognition of the deleterious effects of overactivation of the renin-angiotensin system (RAS) and AT1-Gq/G13 signaling [28][29][30], in addition to desensitization of cardioprotective βAR-Gs signaling [31][32][33], has made RAS a major therapeutic target, whether systemically or regionally [34,35]. In many randomized, controlled trials, ACE inhibitor (ACEi) reduced morbidity and mortality more than comparators in patients with congestive heart failure and coronary heart disease [36][37][38][39][40].…”
Section: Heart Failure and At1 Signalingmentioning
confidence: 99%
“…The difference in times to drug administration may also constitute a major reason for the failure of favorable animal study results on the vasopressin-epinephrine combination 1,5 to translate successfully into the clinical setting. 3,5 In accordance with this interpretation, a previous study reported that the mean time to first drug administration in animal cardiac arrest studies was 9.5 minutes, as opposed to 19.4 minutes in human studies of out-of-hospital cardiac arrest.…”
mentioning
confidence: 99%